Switching From Age-Based Stimulus Dosing to Dose Titration Protocols in Electroconvulsive Therapy: Empirical Evidence for Better Patient Outcomes With Lower Peak and Cumulative Energy Doses. Issue 3 (September 2017) - O'Neill-Kerr, Alex; Yassin, Anhar; Rogers, Stephen; Cornish, Janie
Abstract : Objective: The aim of this study was to test the proposition that adoption of a dose titration protocol may be associated with better patient outcomes, at lower treatment dose, and with comparable cumulative dose to that in patients treated using an age-based stimulus dosing protocol. Methods: This was an analysis of data assembled from archived records and based on cohorts of patients treated respectively on an age-based stimulus dosing protocol and on a dose titration protocol in the National Health Service in England. Results: We demonstrated a significantly better response in the patient cohort treated with dose titration than with age-based stimulus dosing. Peak doses were less and the total cumulative dose was less in the dose titration group than in the age-based stimulus dosing group. Conclusions: Our findings are consistent with superior outcomes in patients treated using a dose titration protocol when compared with age-based stimulus dosing in a similar cohort of patients.